Tanggung Jawab Balai Besar Konservasi Sumber Daya Alam dalam Pencegahan Perambahan Kawasan Hutan Konservasi di Nusa Tenggara Timur - Mau, Ellon Belwan Cornelius; Naatonis, Mathelda (Fakultas Hukum, Universitas Muslim Indonesia, 2023)
This research aims to examine the relationship between the increase in encroachment on conservation forests and the classification of forests based on their ownership status, as well as assess the East Nusa Tenggara BBKSDA's responsibility in addressing conservation forest encroachment. This research uses an empirical legal research method. All collected data is then qualitatively analyzed to describe the problem and answer the research objectives. The results show that land ownership claims, boundary disputes, and a lack of community understanding regarding conservation forest status are the primary causes of encroachment. Although the East Nusa Tenggara BBKSDA has taken various proactive steps to address conservation forest encroachment, the issue has not yet been fundamentally resolved. Therefore, it is recommended that the Local Government and East Nusa Tenggara BBKSDA take concrete measures to tackle the ambiguity of land ownership status, which is one of the root problems of conservation forest encroachment. These measures could begin with reviewing and updating data related to land boundaries and ownership status, followed by mediation between the government and the community to resolve border disputes fairly and transparently. Furthermore, it is essential for traditional institutions and local communities to actively participate in this process actively, utilizing local knowledge and traditions in determining fair and mutually recognized land boundaries. The Local Government and BBKSDA must also enhance efforts to socialize and educate the community about the importance of conservation forests, including the long-term benefits of forest conservation for environmental sustainability and the local economy. These efforts should be carried out through effective communication appropriate to the local cultural context so that the community can accept and value the importance of conservation forests.